2005
DOI: 10.2188/jea.15.228
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Stability of Job Characteristics Scale Scores among a Japanese Working Population

Abstract: BACKGROUND: The job characteristics scale of job strain, which combines high job demands and low decision latitude based on Karasek’s model, has been applied to studies on health care and cardiovascular disease. However, little is known about the long-term stability of this scale with exposure of workers to job. We investigated the 5-year intraindividual variation in job characteristics scores among healthy community workers. METHODS: Subjects of the study were 458 community dwelling persons forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Prior research showed stability for scores of the job content questionnaire on two occasions, before and after an average interval of 6.6 years among 2490 Europeans who remained in the same job (15). In addition, the scores of the work characteristics for the same persons did not change appreciably over a 5-year interval in Japan (36). However, the Japanese study also found that the scores were less stable when there was a position change even within the same company.…”
Section: Discussionmentioning
confidence: 93%
“…Prior research showed stability for scores of the job content questionnaire on two occasions, before and after an average interval of 6.6 years among 2490 Europeans who remained in the same job (15). In addition, the scores of the work characteristics for the same persons did not change appreciably over a 5-year interval in Japan (36). However, the Japanese study also found that the scores were less stable when there was a position change even within the same company.…”
Section: Discussionmentioning
confidence: 93%
“…27 Our colleagues have reported lower levels of CRP in Japanese compared with studies conducted in other Western countries, 28 as well as intra-individual stability of CRP levels over an interval of 5 years. 29 In Western countries, MS is associated with mortality in older women, 3 and with CVD in middle-aged 1,4 and elderly people. 2,5 In diabetic patients, the new definition of MS in Japan was not predictive for CVD in either male or female patients in a prospective study, but a positive relationship according to WHO or NCEP-ATP III criteria was documented.…”
Section: Discussionmentioning
confidence: 99%
“…The present study related job demands at baseline with suicide during an average 9-year follow-up. As the less stable test-retest reliability indicates [43], job demands can change from time to time. Therefore, this study does not exclude the possibility that workers are at higher risk of suicide when they work extremely long hours or under extremely high job demands.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach’s coefficient alphas for the job control index and psychological demand index were 0.65 and 0.69, respectively. Job characteristics were also assessed as part of this cohort during the follow-up, demonstrating a moderate degree of stability with 5-year interval correlations of 0.63 (n = 377) for job control and 0.57 (n = 378) for job demands [43]. The variables were divided in such a way that the most adverse tertile indicated low control or high demands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation